Detection of urinary microRNA biomarkers using diazo sulfonamide-modified screen printed carbon electrodes. Issue 31 (25th May 2021) - Smith, Daniel A.; Simpson, Kate; Lo Cicero, Matteo; Newbury, Lucy J.; Nicholas, Philip; Fraser, Donald J.; Caiger, Nigel; Redman, James E.; Bowen, Timothy
Abstract : In this study we have developed an electrochemical microRNA biosensor sensitive to 17 fM and capable of detecting an established downregulation of urinary miR-192 in diabetic kidney disease patients. Abstract : This paper describes a straightforward electrochemical method for rapid and robust urinary microRNA (miRNA) quantification using disposable biosensors that can discriminate between urine from diabetic kidney disease (DKD) patients and control subjects. Aberrant miRNA expression has been observed in several major human disorders, and we have identified a urinary miRNA signature for DKD. MiRNAs therefore have considerable promise as disease biomarkers, and techniques to quantify these transcripts from clinical samples have significant clinical and commercial potential. Current RT-qPCR-based methods require technical expertise, and more straightforward methods such as electrochemical detection offer attractive alternatives. We describe a method to detect urinary miRNAs using diazo sulfonamide-modified screen printed carbon electrode-based biosensors that is amenable to parallel analysis. These sensors showed a linear response to buffered miR-21, with a 17 fM limit of detection, and successfully discriminated between urine samples ( n = 6) from DKD patients and unaffected control subjects ( n = 6) by differential miR-192 detection. Our technique for quantitative miRNA detection in liquid biopsies has potential for development as a platform for non-invasive high-throughput screening and/or to complement existing diagnostic procedures in disorders such as DKD.